Prevalence of Symptoms of Anxiety Among Residents of Kabul During Pandemic of COVID-19: A Report from Capital of Afghanistan - Rasib AR (Dove Medical Press, 2021)
Aziz Rahman Rasib,1 Arash Nemat,2,3 Mahmoodullah Azimi,4 Naqeebullah Zaki,5 Mohammad Faiq Sediqi,6 Nahid Raufi,7 Abdullah Asady2 1Department of Neuropsychiatry, Kabul University of Medical Sciences, Kabul, Afghanistan; 2Department of Microbiology, Kabul University of Medical Sciences, Kabul, Afghanistan; 3Department of Cardiology, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 4Department of Clinical Pharmacology, Kabul University of Medical Sciences, Kabul, Afghanistan; 5Department of Public Health, Tata Institute of Social Sciences, Mumbai, India; 6Department of Histology, Kabul University of Medical Sciences, Kabul, Afghanistan; 7Department of Dermatology, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Abdullah AsadyDepartment of Microbiology, Kabul University of Medical Sciences, Kabul, AfghanistanTel +93 731087928Email asady_abdullah@yahoo.comPurpose: This study was conducted to evaluate the prevalence of symptoms of anxiety among residents of Kabul during the present COVID-19 pandemic.Methods: This descriptive cross-sectional, community based survey was conducted in Kabul, Afghanistan, during the COVID-19 pandemic. Data were collected from July 11, 2020, to July 16, 2020. A bilingual (Dari and English) questionnaire was used for data collection. The first section of the questionnaire collected sociodemographic information of the respondents and the second comprised a self-report standardized scale, i.e. Generalized Anxiety Disorder-7 (GAD-7) to assess symptoms of anxiety. The survey form was distributed through online platforms. All residents of Kabul who used social apps such as WhatsApp and Facebook were eligible to participate in the study and participation was voluntary and non-commercial.Results: Altogether 1135 complete responses were received. The majority of them were males and aged 18– 34 years. Almost 18% were healthcare workers. Overall, 28.2% of the respondents reported symptoms of moderate to severe anxiety, 38.8% reported symptoms of mild anxiety, and nearly one third of the respondents reported no symptoms. Female participants reported significantly higher levels of anxiety compared with males (39.7% versus 25.6%; p = 0.0001). No significant association was noted between anxiety levels and age groups, occupations, and healthcare workers versus non-healthcare workers.Conclusion: The findings suggest that a gender-specific psychosocial protocol needs be integrated into the public health emergency plans to fight against the current pandemic.Keywords: anxiety, mental health, capital of Afghanistan, Kabul, COVID-19 pandemic